Discovery of napabucasin derivatives for the treatment of tuberculosis. Issue 9 (30th July 2019) - Li, Chungen; Tang, Yunxiang; Sang, Zitai; Yang, Yang; Gao, Yamin; Yang, Tao; Fang, Cuiting; Zhang, Tianyu; Luo, Youfu
Abstract : Thirty-one napabucasin derivatives were synthesized and evaluated for their antitubercular activities, as well as for studying the structure–activity relationships. Abstract : Tuberculosis is the contagious disease responsible for the highest number of deaths worldwide. Here, we screened a commercially available compound library and found napabucasin to possess a moderate anti-tubercular activity against M. tuberculosis H37Ra (MIC 2.5 μg mL −1, 10.4 μM). Three series of napabucasin derivatives were further evaluated for their in vitro anti-tubercular activities against Mtb H37Ra. The activity of most derivatives was either retained or enhanced compared with that of napabucasin. Compound3s was the most active compound showing a MIC value of 0.3125 μg mL −1 (0.9 μM). Furthermore, several compounds were selected and evaluated against the Mtb H37Rv standard strain and six Mtb clinical isolates. Importantly, these compounds were found to be effective against Mtb clinical isolates with multi-resistance to isoniazid, rifampicin, and ethambutol.